Multi-Layered Pawning in Agrarian Indonesia: Islamic Legal Challenges and Sustainable Development Implications: Gadai Bertingkat dalam Masyarakat Agraris Indonesia : Dinamika Hukum Islam dan Implikasi bagi Pembangunan Berkelanjutan - Jannah, Nurfaidatul; Rahyu, Putri; Mulyati, Suci; Aisya , Hana Putri (Az-Zarqa’: Jurnal Hukum Bisnis Islam, 2024)
Abstract: This study examines the practice of multi-layered pawning in Rato Village, Bima Regency, Indonesia, which is frequently conducted without formal written agreements, thus posing risks to the original landowner (rāhin). This practice typically involves the transfer of pawned land to a third party without the knowledge or consent of the land pawn initiator (first party), placing the rāhin in a vulnerable economic position. From an Islamic legal perspective, this multi-layered pawning practice raises fundamental issues related to principles of justice, transparency, and property rights protection, which are core tenets in Shariah. Initially, this practice was considered part of ‘urf (custom) that was socially accepted. However, as it increasingly causes harm to the rāhin, it transforms into ‘urf fāsid (harmful custom), which is incompatible with Shariah principles due to its violation of justice. This research employs a qualitative method with a descriptive-analytical approach, involving in-depth interviews with local community members, village leaders, and an analysis of literature on Islamic law and sustainable development concepts. The findings reveal that multi-layered pawning not only impacts the economic stability of the landowner but also threatens the economic, social, and environmental sustainability of agrarian communities in the region. The study recommends reforms through formal regulations involving village authorities as supervisors. With strict oversight, formalized written agreements, and robust education in Shariah financial literacy, pawning practices can be directed to support fair economic sustainability for agrarian communities. This research contributes to the study of pawning law in Indonesia and provides a policy reference for enhancing welfare and economic sustainability within agrarian societies. Abstrak: Penelitian ini mengkaji praktik gadai bertingkat di Desa Rato, Kabupaten Bima, Indonesia, yang sering dilakukan tanpa perjanjian tertulis, sehingga menimbulkan risiko bagi pemilik tanah asli (rāhin). Praktik ini umumnya melibatkan pengalihan lahan gadai kepada pihak ketiga tanpa sepengetahuan atau persetujuan penggadai tanah (pihak pertama), yang menempatkan penggadai tanah (rāhin) dalam posisi ekonomi yang rentan. Dalam perspektif hukum Islam, praktik gadai bertingkat ini menimbulkan masalah mendasar yang berkaitan dengan prinsip keadilan, transparansi, dan perlindungan hak milik, yang merupakan prinsip utama dalam syariah. Awalnya, praktik ini dianggap sebagai bagian dari ‘urf (kebiasaan) yang diterima secara sosial. Namun, ketika praktik ini mulai merugikan rāhin, statusnya berubah menjadi ‘urf fasid (kebiasaan yang merusak/merugikan), yang tidak sesuai dengan prinsip syariah karena melanggar prinsip keadilan. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif-analitis, melibatkan wawancara mendalam dengan masyarakat lokal, tokoh desa, serta analisis literatur terkait hukum Islam dan konsep pembangunan berkelanjutan. Temuan dalam penelitian ini menunjukkan bahwa gadai bertingkat tidak hanya berdampak pada stabilitas ekonomi penggadai tanah, tetapi juga mengancam keberlanjutan ekonomi, sosial dan lingkungan komunitas agraris di wilayah tersebut. Studi ini merekomendasikan adanya reformasi melalui regulasi formal yang melibatkan pemerintah desa sebagai pengawas. Dengan pengawasan ketat, perjanjian tertulis, dan edukasi literasi keuangan syariah yang baik, praktik gadai dapat diarahkan untuk mendukung keberlanjutan ekonomi yang adil bagi masyarakat agraris. Penelitian ini berkontribusi pada kajian hukum gadai di Indonesia dan menawarkan acuan kebijakan bagi kesejahteraan dan keberlanjutan ekonomi di masyarakat agraris.